Recent Progress of Polarization‐Sensitive Perovskite Photodetectors - Hou, Hong‐Yi; Tian, Shuo; Ge, Heng‐Ru; Chen, Jing‐De; Li, Yan‐Qing; Tang, Jian‐Xin (Advanced functional materials, 2022)
Polarization‐sensitive photodetectors are gaining numerous attention since polarization detection is important in geological remote sensing, atmospheric monitoring, military recon, and medical examination. Among various reported photoactive materials for photodetectors, metal halide perovskites have outstanding advantages such as tunable band gaps, excellent optoelectronic properties, and easy fabrication. Moreover, the characteristics of crystal structure anisotropy and controllable growth orientation of perovskite crystals endow the perovskite photodetector with the ability to identify light polarization states. This review outlines the recent research progress of perovskite photodetectors on polarization‐sensitive detection. Firstly, key device parameters of polarization‐sensitive detection are introduced. Then, the recent progress of polarization‐sensitive perovskite detectors in the field of linear and circular polarization is reviewed according to the different principles of polarization response. Finally, the challenges of polarization‐sensitive perovskite photodetector are discussed. Polarization‐sensitive photodetectors are important in geological remote sensing, atmospheric monitoring, military recon, and medical examination. The review addresses the recent research progress of perovskite photodetectors on polarization‐sensitive detection in terms of key device parameters, linear and circular polarization via different principles of polarization response.